Looking Beyond the Fiscal : Do Oil Funds Bring Macroeconomic Stability? - Shabsigh, Ghiath (IMF Working Papers; Working Paper ;, 2007)
Oil funds have become increasingly popular in oil exporting countries during the recent surge in oil prices. However, the literature on the contribution is small, tends to focus narrowly on their fiscal benefits, and concludes that they are redundant of such funds-in other words, that well designed fiscal management and policy are adequate substitutes for oil funds. This paper argues that a broader focus is needed in judging the effectiveness of such funds. We test whether oil funds help reduce macroeconomic volatility. The econometric estimation results from a 30-year panel data set of 15 countries with and without oil funds suggest that oil funds are associated with reduced volatility of broad money and prices and lower inflation. However, there is a statistically weak negative association between the presence of an oil fund and volatility of the real exchange rate.